2009
DOI: 10.1002/jcop.20339
|View full text |Cite
|
Sign up to set email alerts
|

Community violence exposure and aggression among urban adolescents: testing a cognitive mediator model

Abstract: Past research has shown that exposure to violence leads to aggressive behavior, but few community-based studies have examined theoretical models illustrating the mediating social cognitive processes that explain this relation with youth exposed to high rates of violence. This study examines the impact of community violence on behavior through cognitive mediators: normative beliefs about aggression and self-efficacy to control aggression. Self-report surveys were completed by two samples (cross-sectional and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 37 publications
6
60
1
2
Order By: Relevance
“…Given that aggressive attitudes have been established as a mediator of the association between exposure to violence and perpetrating aggressive and violent behavior, both in previous studies (e.g., Guerra et al, 2003;McMahon, Felix, Halpert, & Petropoulos, 2009) and in the current study, identifying factors that can reduce the impact of violence on youths' attitudes is an important step in understanding and reducing the effects of violence. This study focused on attachment security because the working models associated with secure attachment may counteract the tendency for witnesses of aggression to view it as normative or acceptable.…”
Section: Discussionmentioning
confidence: 74%
“…Given that aggressive attitudes have been established as a mediator of the association between exposure to violence and perpetrating aggressive and violent behavior, both in previous studies (e.g., Guerra et al, 2003;McMahon, Felix, Halpert, & Petropoulos, 2009) and in the current study, identifying factors that can reduce the impact of violence on youths' attitudes is an important step in understanding and reducing the effects of violence. This study focused on attachment security because the working models associated with secure attachment may counteract the tendency for witnesses of aggression to view it as normative or acceptable.…”
Section: Discussionmentioning
confidence: 74%
“…Las conductas agresivas y delictivas pueden aumentar en forma continua (Gaylord-Harden, So, Bai, Henry, & Tolan, 2017), lo que se ha relacionado con creencias que justifican la violencia como forma de protección y una disminución de la autoeficacia para el control de la agresión (McMahon, Felix, Halpert, & Petropoulos, 2009). Además, se hna encontrado diferencias en la sintomatología de acuerdo con la relación que mantiene el adolescente con la víctima: mayor nivel de depresión cuando es un familiar y mayor nivel de ansiedad cuando es un amigo o conocido (Lambert, Boyd, Cammack, & Ialongo, 2012).…”
Section: Introductionunclassified
“…In addition, several researchers have proposed that cognitive factors, such as moral disengagement, play a central role in the relationship between trauma exposure and aggressive behavior among inner-city African American youth (McMahon, Felix, Halpert, & Petropoulos, 2009). Exposure to trauma could lead to the development of a pathological adaptation to violence (Ng-Mak et al, 2002; Ng-Mak, Salzinger, Feldman & Stueve, 2004) and to deceased self-efficacy to handle social problems in an effective, non-aggressive manner (LeBlanc, Self-Brown, Shepard, & Kelly, 2011; McMahon, Todd, Martinez, Coker, Sheu, Washburn, & Shah, 2013) .…”
mentioning
confidence: 99%
“…McMahon and colleagues (2009) investigated the impact of community violence exposure on aggressive behavior through two cognitive mediators: normative beliefs about aggression and self-efficacy to control aggression. This study found that exposure to community violence was significantly associated with retaliatory beliefs supporting aggression among a sample of African American youth (McMahon et al, 2009). …”
mentioning
confidence: 99%
See 1 more Smart Citation